Efektivitas Penggunaan Media Kartu Huruf Terhadap Kemampuan Menulis Permulaan Huruf A-Z pada Anak Autis Kelas II di SLB Negeri Pembina Kupang - Wangge, Vinsesius; Selan, Ot Bil Wilson; Nabunome, Carolin; Lobain, Desy Riyani; Damamijuk, Ernawati Rambu; Ndun, Fingki Apriliana; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2026)
The urgency of this study lies in the problems faced by autistic children in relation to their writing abilities. The purpose of this study is to determine the effectiveness of using letter cards in improving the ability of autistic children to write the letters A–Z. The method used in this study is classroom action research (CAR), which was conducted in two cycles consisting of planning, action, observation, and reflection. The subjects of this study were second-grade students at SLBN Pembina Kupang. The results of this study indicate that the ability to write letters A-Z increased significantly after using letter cards. In each cycle, data were collected through initial and final tests, as well as observations of student learning activities. At the end of cycle II, the students' average scores increased significantly, demonstrating the effectiveness of using letter cards in supporting the learning process. The conclusion of this study is that letter cards can be an effective and efficient medium for improving early writing skills in children with autism.